Professional Development Appraisal And Teacher Performance Among Secondary Schools In Migori County (International Journal of Scientific Research and Management (IJSRM), 2021)
Performance appraisal forms an important practice in human resource management. In Kenya, the Teacher Performance Appraisal and Development (TPAD) has been used since 2012 as an appraisal approach to evaluate teachers’ performance. However, the effectiveness of performance appraisal in enhancing teacher productivity as reflected in students; academic achievement has not been documented in Kenya and remains questionable. In Migori County, student performance in KCSE examination has been comparatively low. The objective of this study was to analyse the influence of professional development appraisal on teacher performance among public secondary schools in Migori County. Specific objectives were to determine the level of teachers’ performance after evaluation, and to establish how appraisal of professional development influence performance of teachers. Descriptive survey design on a target population of 276 principals and 2961 teachers was employed in the study. Krejcie and Morgan (1970) table was adopted to derive a sample size of 342 teachers and 57 principals stratified based on school category population. Questionnaire and interview guide were used to collect data from teachers and principals respectively. The study found that there was a significant difference in the mean of teacher’s performance after appraisal and the category of teachers’ schools. The study also found that 64.1% changes in teachers’ performance is attributed to professional development appraisal (R2 =0.641), and that professional development appraisal (β=0.803) is a significant predictor of teacher performance F (1, 278) =493.200, P<0.05. The study concludes that professional development appraisal significantly contributes to performance of teachers in secondary schools.